2012
DOI: 10.1089/ast.2012.0861
|View full text |Cite
|
Sign up to set email alerts
|

The O/OREOS Mission: First Science Data from the Space Environment Viability of Organics (SEVO) Payload

Abstract: We report the first science results from the Space Environment Viability of Organics (SEVO) payload aboard the Organism/Organic Exposure to Orbital Stresses (O/OREOS) free-flying nanosatellite, which completed its nominal spaceflight mission in May 2011 but continues to acquire data biweekly. The SEVO payload integrates a compact UV-visible-NIR spectrometer, utilizing the Sun as its light source, with a 24-cell sample carousel that houses four classes of vacuum-deposited organic thin films: polycyclic aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 38 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Radich et al (2014) have shown that, in aqueous media, UV-generated OH radicals trigger graphene (very large PAHs) scission into smaller, PAH-like compounds that, with continued irradiation, produce CO 2 and H 2 O. Likewise, Mattioda et al (2012), who studied PAH photochemistry in different environmental cells, show that the loss of the PAH isoviolanthrene (C 34 H 18 ) with growth of CO 2 occurs only water vapor is present in the chamber.…”
Section: Pah/h 2 O-ice Photochemistry Photoproducts and Astrochemistrymentioning
confidence: 99%
“…Radich et al (2014) have shown that, in aqueous media, UV-generated OH radicals trigger graphene (very large PAHs) scission into smaller, PAH-like compounds that, with continued irradiation, produce CO 2 and H 2 O. Likewise, Mattioda et al (2012), who studied PAH photochemistry in different environmental cells, show that the loss of the PAH isoviolanthrene (C 34 H 18 ) with growth of CO 2 occurs only water vapor is present in the chamber.…”
Section: Pah/h 2 O-ice Photochemistry Photoproducts and Astrochemistrymentioning
confidence: 99%
“…The experiment SEVO used a triple-cube satellite Mattioda et al 2012), whereas the experiment Perseus took place on the Mir station and the experiments PROCESS, AMINO and ORGANIC on Expose-E or Expose-R onboard the ISS (Boillot et al 2002;Bertrand et al 2012;Cottin et al 2012;Noblet et al 2012). Different organic compounds were thus exposed, including amino acids and their derivatives, peptides, nucleic bases, polymers (polyoxymethyl, polyacrylonitrile, polycyclic aromatic hydrocarbons PAH, tholins, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As a direct result of these advances and the concomitant advances achieved through complementary studies involving astronomical observations of DIBs, laboratory simulation of interstellar analogs for neutral and ionized PAHs (Salama 2008 and references therein; Salama et al 2011;Gredel et al 2011), space exposure experiments of PAHs (Ehrenfreund et al 2007;Bryson et al 2011;Mattioda et al 2012), theoretical calculations of PAH spectra (Weisman et al 2003;Ruiterkamp et al 2005) and the modeling of diffuse and translucent interstellar clouds (Snow and McCall 2006 and references therein) it has become possible to further test the validity of the 'PAH-DIB' proposal.…”
Section: Introductionmentioning
confidence: 99%